Visual Branding and Its Impact on the Corporate Image (Al-Academy, 2026)
The study concluded that advertisement design serves as the cornerstone in building both the visual brand identity and the corporate image of an organization, functioning as a strategic tool that is indispensable for enhancing the institution's presence in the market. The findings revealed that successfully establishing a strong visual brand requires smart and integrated planning of advertising activities, beginning with logo design and extending to the finest details of the advertising campaign, ensuring consistency between visual messaging and organizational goals. It was also confirmed that commitment to visual identity contributes to delivering positive messages that reflect the institution’s credibility and the quality of its services, ultimately shaping a positive corporate image that reinforces audience trust and loyalty.In light of these findings, the study recommends that business institutions invest in developing a distinctive visual identity managed through effective strategic planning, thereby enhancing their competitive edge both locally and globally. Furthermore, it advocates for the inclusion of specialized courses in visual branding and corporate image within art and media college programs, given the growing significance of these fields in modern communication and marketing environments. The study also emphasizes the importance of advancing scientific research in this domain to enrich both theoretical and practical knowledge, and to address the evident shortage of specialized literature on visual identity and advertising.